Comparison of Cortisol and Some Physiological Biomarkers Among Athletes Following a Basketball Sports Performance - Hamid Mohammed Saeed, Iktefa Abdul; Salih, Abdulrahman Aeed; Abdulkareem, Saman Muhsin (Bangladesh Journal of Medical Science, 2023)
The current study was designed to investigate the effect of exercise on the level of the cortisol hormone and some physiological variables in male athletes. The cortisol, vitamin C, glutathione (GSH), and malondialdehyde (MDA) levels in the serum of twenty young male basketball players were measured before and after the exercise. The cortisol values and GSH levels showed a statistically significant decrease after physical effort compared to the result before training, in contrast to vitamin C and MDA levels represent a statistically significant increase. Decreasing cortisol levels after activity showed decreasing stress because exercise for years will reduce the stimulating effect of cortisol secretion. In addition, in response to increased oxidative stress caused by exercise, serum vitamin C increased to prevent oxidative stress. As a result, training in these athletes led to producing reactive oxygen species and thus increased lipid peroxidation, which increased MDA levels by exhausting the antioxidant defense system and reducing GSH levels. Measurement of these biomarkers allows the identification of players affected by severe oxidative stress and indicates the time of intervention for improving their performance and health. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.127-132